Analysis of Realization of Total Connected Power By Industrial Customer Using K-Means Clustering Method - Tri Febri Damayanti; M. Safii (Asosiasi Perguruan Tinggi Informatika dan Ilmu Komputer (APTIKOM) Provinsi Sumatera Utara, 2023)
Electrical power is one of the primary needs for living things, especially humans. With the existence of electrical energy, human activities are getting easier and more practical. This study aims to assist the relevant government, especially PLN in the province of North Sumatra, in knowing the quality and quantity of actual connected power in the province of North Sumatra. Completion of cases in this study using the K-Means Clustering Data Mining Method. The data used in this study were obtained directly through the Central Statistics Agency (BPS) website for North Sumatra province with the url https://bps.sumut.go.id. The analysis in this study uses 2 (two) cluster levels, namely high realization (C1) and low realization (C2). The research results obtained are that there is 1 area that is included in the high cluster (C1) and there are 9 areas that are included in the low cluster (C2). It is hoped that the research results can become input, suggestions and efforts for the government, especially PLN in North Sumatra province to pay more attention to and increase the realization of electricity connected power in areas that are included in low clusters so that industrial processes can run effectively and efficiently and can support economic growth in the province of North Sumatra.